M Mitigasi Mission Drift Melalui Organisasi Hibrida Pastoral: Peran Tata Kelola Internal, Kerja Kolaboratif, dan Roadmap Strategis: - - Hipolitus Kristoforus Kewuel (Jurnal Pelayanan Pastoral, 2026)
This study examines how organizations with alternative pastoral systems strive to achieve financial independence as a corrective to conventional pastoral care, which has long relied on external funding. On the one hand, charitable work under this system must manage conflicts arising from the demands of business professionalism. On the other hand, it must also uphold social welfare through compassionate services. Thus, this approach develops a governance framework that enables organizations to operate professionally while safeguarding the core of their mission. The researcher employs a case study method to analyze data from four distinct pastoral services: orphanages, schools, student dormitories, and hospitals. The findings reveal three fundamental elements that establish a balance between professional conduct and compassionate service. First, establishing internal governance to protect both social and commercial cash flows. Second, establishing a governance system that allows business personnel to develop the essential skills required by industry standards. Third, establishing a strategic framework that functions as a “moral constitution” to guide both business success and social objectives, ensuring that underprivileged communities receive special assistance through cross-subsidy programs.